Upaya Guru Bimbingan Dan Konseling Dalam Menangani Peserta Didik Yang Membolos - Nuriman, Puspita; Irfani, Amalia; ., Barriyati (Counseling AS SYAMIL: Jurnal Ilmiah Bimbingan Konseling Islam, 2021)
Abstract: Ditching is the act of students not attending school without a clear explanation. This study aims to reveal how the strategies, actions and the level of success of the strategies and actions taken by BK teachers against students skipping school. This research is a type of descriptive research with a qualitative approach. The data sources of this study consisted of primary sources, namely 1 BK teacher, and secondary sources of 5 students. The technique of collecting data is direct communication to both primary and secondary sources with interview guidelines, then using observation and documentation techniques. The analysis of the discussion is that the BK teacher makes a strategy by making a letter of agreement or a contract of punishment, by providing individual or group counseling services as well as providing punishment in accordance with the contract agreement. The success of these strategies and actions provides a deterrent effect to students, so that students do not take truant action again.